(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper delves into Isaac Asimov’s prescient abilities as a creator, specifically his anticipation of the 21st century in his quick tale "The Fun They Had." Through a thorough analysis of the tale’s issues, characters, and technological predictions, this paper examines Asimov’s uncanny foresight into the future of training and technology. By exploring the parallels between Asimov’s fictional global and cutting-edge society, this paper sheds light on the long-lasting relevance of his work and its implications for our knowledge of the existing and destiny.